An Afro-Asian nexus: South African multinational firm experiences in Chinese labour markets – key focus areas - F. Horwitz; M. Ferguson; I. Rivett; A. Lee (South African Journal of Business Management, 2005)
This exploratory study examines perspectives of multinational corporations (MNCs) from South Africa (SA) in respect of the variables considered important in product and labour markets in China. These include how MNCs first interpret and understand cultural, human capital, regulatory factors and employment practices, before considering how they might adapt to or seek to influence them. A survey of thirteen SA firms operating or trading in these markets and interviews with South Africans who had undertaken exploratory assignments in China, were done. Key factors were identified and evaluated based on relevant literature and research. The following six focus areas were found to be important for business effectiveness in this market: understanding its market complexity, importance of joint venture partners, guanxi relationship networks, human capital, language and culture, and regulatory environment.
Keywords: 650